2013
DOI: 10.4103/2225-4110.119720
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamic Responses to Acupuncture in Migraine Patients: A Systematic Review

Abstract: We review the literature conjoining acupuncture, migraine, and cerebral hemodynamics. To do so, we searched PubMed in March 2013 for studies investigating cerebral hemodynamics with functional magnetic resonance imaging (fMRI), near-infrared spectroscopy (NIRS), transcranial Doppler (TCD) ultrasound, and other tools in migraineurs, acupuncture recipients, and migraineurs receiving acupuncture. Our search identified 1321 distinct articles – acupuncture (n = 463), migraine (n = 866), and both (n = 8). Only three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our query on June 9, 2014, produced ( n = 18) results. We excluded ( n = 3) reviews [ 10 , 43 , 44 ]. From a review, an additional three candidates, not covered in the database search, were added for consideration, of which only one was obtained and included [ 27 , 44 – 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our query on June 9, 2014, produced ( n = 18) results. We excluded ( n = 3) reviews [ 10 , 43 , 44 ]. From a review, an additional three candidates, not covered in the database search, were added for consideration, of which only one was obtained and included [ 27 , 44 – 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the findings above indicate that the cerebral tissue oxygenation response to acupuncture, even in healthy young adults, varies widely, with no clear correlation to any single factor. Further research is required to investigate whether the variation in response carries over to subjects exhibiting dysfunction in cerebral autoregulation, as in stroke or migraine, since acupuncture has been found to have modulating effects [ 10 , 47 ]. We recommend that future investigations consider the following for control: population age and fitness/health level; acupuncture type and intensity of stimulation (number of sessions, frequency, and duration); and NIRS machine model and recorded parameters and the number and positioning of probe(s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that migraine is characterized by elevated intracranial blood flow velocity and pulsatile headaches, TCD detection of intracranial hemodynamic changes can be used to evaluate the improvement of migraine symptoms (47). We, therefore, employed a meta-analysis to analyze the influence of treatment (acupuncture or medication) on intracranial blood flow changes as measured by TCD (Figure 4).…”
Section: Tcdmentioning
confidence: 99%
“…Neuroimaging studies show that acupuncture can calm areas of the brain that register pain and activate those involved in down regulating the stress response . Doppler ultrasound has shown that acupuncture increases blood flow in treated areas (Lo, Lin, Wei, & Sun, 2013). Finally, thermal imaging shows that acupuncture can decrease inflammation (Santos et al, 2013;Stux, Berman, & Pomeranz, 2000).…”
Section: Acupuncturementioning
confidence: 99%